PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT. MITRA SARANA MEMBANGUN DI PANGKALAN KERINCI - Yusuf Abdi; Marzolina Marzolina; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the influence of leadership and compensation on jobsatisfaction of employees of PT. Mitra Means Building in Pangkalan Kerinci. Thepopulation in this study were all employees of PT. Mitra Sarana Building inPangkalan Kerinci totaling 145 people. The analytical method used is multiplelinear regression with the help of SPSS program. The results of this study indicatethat leadership has a positive and significant effect on job satisfaction;compensation has a positive and significant effect on job satisfaction; leadershipand compensation have a positive and significant effect simultaneously on jobsatisfaction. Keywords : Leaderships, Compensation, and Job Satisfaction